Existence of Solutions for Nonlinear Impulsive Fractional Differential Equations of Order α∈(2,3] with Nonlocal Boundary Conditions - Lihong Zhang; Guotao Wang; Guangxing Song (Abstract and Applied Analysis)
We investigate the existence and uniqueness of solutions to the nonlocal boundary value problem for nonlinear impulsive fractional differential equations of order α∈(2,3]. By using some well-known fixed point theorems, sufficient conditions for the existence of solutions are established. Some examples are presented to illustrate the main results.